2015
DOI: 10.4103/2230-8598.153829
|View full text |Cite
|
Sign up to set email alerts
|

Janani Suraksha Yojana : Its utilization and perception among mothers and health care providers in a rural area of North India

Abstract: Janani Suraksha Yojana: Its utilization and perception among mothers and health care providers in a rural area of North IndiaBackground: Janani Suraksha Yojana (JSY) is a maternal protection scheme that promotes institutional delivery by providing cash incentive to the mothers who deliver their babies in a health facility. With the purpose of improving maternal and neo-natal mortality and morbidity indicators, the investment and emphasis on JSY is continued. Utilization pattern and perception in the community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 3 publications
0
12
2
Order By: Relevance
“…7 Our study result is higher than study conducted by Harpreet Kaur, et al (48.2%), Vikram K, et al (27.3%), and lower than study by Raut M M, et al (80.3%). [8][9][10] In present study 68% of mothers had utilized Anganwadi Nutrition Supplementation which is lower than study by Jawahar Preethy, et al (74.1%).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…7 Our study result is higher than study conducted by Harpreet Kaur, et al (48.2%), Vikram K, et al (27.3%), and lower than study by Raut M M, et al (80.3%). [8][9][10] In present study 68% of mothers had utilized Anganwadi Nutrition Supplementation which is lower than study by Jawahar Preethy, et al (74.1%).…”
Section: Discussioncontrasting
confidence: 56%
“…7,8 The present study was undertaken to assess the utilization and their determinants for various maternity benefit schemes among urban slum population of Davangere city.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study 83.20 % JSY beneficiaries were escorted by ASHA during delivery but as few as 17% used the vehicle facility. In studies [8,9,10] escorting was reported between 40-70%. This could be because the slum where the study was undertaken was located in heart of city and modes of communication were very good.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Vikas Kumar etal, reveals that postnatal visits at home by ASHAs were 100.00% in institutional deliveries and 48.00% in home deliveries [10] . ASHAs thus are potential resource for reducing maternal and neonatal mortality after training in postnatal check-up in near future.…”
Section: Discussionmentioning
confidence: 99%
“…5 It was found that 79.39% JSY beneficiaries were escorted by ASHA and rent of vehicle was paid by ASHA to 48.09% beneficiaries. All the beneficiaries (100%) received cash incentive.…”
Section: Review Of Literaturementioning
confidence: 99%